The Cambridge companion to Christianity and the environment - Hampton, Alexander J. B. ca. 20./21. Jh.; Hedley, Douglas (Cambridge companions to religion, 2022)
"A range of developments, including the growth of the environmental humanities, recent critiques of secularism and the development of the notion of post secularity, and the so-called ontological turn in cultural history and anthropology, have all renewed interest in the way that religions, and particularly Christianity have shaped our collective relationship with, and understanding of, the natural environment. This Cambridge Companion addresses this renewed interest in an interdisciplinary manner. It brings together contributors from the disciplines of classics, English, environmental ethics, literary studies, history, the history and philosophy of science, philosophy, religious studies, and theology. The chapters that make up this volume offer original contributions to this fascinating and important topic that are accessible to university-level students and readers"--